Complete Mitochondrial genome of an equine intestinal parasite, Triodontophorus brevicauda (Chromadorea: Strongylidae): the first characterization within the genus. Issue 5 (October 2015) - Duan, Hong; Gao, Jun-Feng; Hou, Mei-Ru; Zhang, Yan; Liu, Ze-Xuan; Gao, De-Zhen; Guo, Dong-Hui; Yue, Dong-Mei; Su, Xin; Fu, Xue; Wang, Chun-Ren
Abstract: The complete mitochondrial (mt) genome sequence of Triodontophorus brevicauda, an intestinal equine nematode parasite was determined for the first time. The circular T. brevicauda mt genome is 14, 305 bp in length and contains 36 genes, of which 12 code for protein, 22 for transfer RNA, and two for ribosomal RNA, and lacks atp 8 mtDNA gene. Phylogenetic analysis based on the concatenated amino acid sequence of the 12 protein-coding genes was performed using three different tree-building methods. The Strongyloidea cluster divides into two large branches, and each nematode family included in our study forms an independent clade, though paraphyly confounds the issue at some nodes. T. brevicauda clusters together with Cylicocyclus insignis with high statistical support. The mtDNA data in this study not only provide a new mtDNA resource for phylogeny, but also become a novel and useful genetic marker for further studies on the identification, population genetics, and molecular epidemiology of the genus Triodontophorus in equine. Highlights: The complete mitochondrial sequence of Triodontophorus brevicauda was determined. The complete mtDNA sequence of Triodontophorus brevicauda was 14, 305 bp in length. T. brevicauda clustered together with Cylicocyclus insignis in phylogenetic analyses with high statistical support.